Deletion of adipocyte prohibitin 1 exacerbates high‐fat diet‐induced steatosis but not liver inflammation and fibrosis. Issue 12 (5th October 2022) - Wang, Xiaolin; Kim, Seung‐Jin; Guan, Yukun; Parker, Richard; Rodrigues, Robim M.; Feng, Dechun; Lu, Shelly C.; Gao, Bin
Abstract: Adipose tissue dysfunction is closely associated with the development and progression of nonalcoholic fatty liver disease (NAFLD). Recent studies have implied an important role of prohibitin‐1 (PHB1) in adipose tissue function. In the current study, we aimed to explore the function of adipocyte PHB1 in the development and progression of NAFLD. The PHB1 protein levels in adipose tissues were markedly decreased in mice fed a high‐fat diet (HFD) compared to those fed a chow diet. To explore the function of adipocyte PHB1 in the progression of NAFLD, mice with adipocyte‐specific (adipo) deletion of Phb1 ( Phb1 adipo−/− mice) were generated. Notably, Phb1 adipo−/− mice did not develop obesity but displayed severe liver steatosis under HFD feeding. Compared to HFD‐fed wild‐type (WT) mice, HFD‐fed Phb1 adipo−/− mice displayed dramatically lower fat mass with significantly decreased levels of total adipose tissue inflammation, including macrophage and neutrophil number as well as the expression of inflammatory mediators. To our surprise, although liver steatosis in Phb1 adipo−/− mice was much more severe, liver inflammation and fibrosis were similar to WT mice after HFD feeding. RNA sequencing analyses revealed that the interferon pathway was markedly suppressed while the bone morphogenetic protein 2 pathway was significantly up‐regulated in the liver of HFD‐fed Phb1 adipo−/− mice compared with HFD‐fed WT mice. Conclusion : HFD‐fed Phb1 adipo−/− mice display a subtype of the lean NAFLD phenotype with severe hepatic steatosis despite low adipose mass. This subtype of the lean NAFLD phenotype has similar inflammation and fibrosis as obese NAFLD in HFD‐fed WT mice; this is partially due to reduced total adipose tissue inflammation and the hepatic interferon pathway. Abstract : Schematic illustration of the proposed role of adipocyte PHB1 in HFD‐induced NAFLD.image